THE CORRELATION BETWEEN STUDENTS’ READING COMPREHENSION TOWARD STUDENTS’ ENGLISH ACADEMIC ACHIEVEMENT - Susanti, Elly; Irmadila, Dionesia (IKIP PGRI Pontianak, 2018)
This research was aimed to investigate the significance of correlation between students’ reading comprehension toward students’ English academic achievement. The population was the second grade students. By using cluster random sampling, XI IPA 1 and XI IPS 2 were being the sample. The total number of population was 195 students and the total number of sample was 66 students. Written test framed by the aspects of reading comprehension was applying to figure out the students’ reading comprehension score. Documentation technique of students’ English report book was applying to figure out the students’ English academic achievement score. The result shows that there is a significant correlation between students’ reading comprehension and students’ English academic achievement. It is implied the students’ who got higher in reading comprehension test tend to get outstanding score also in their English academic achievement. In addition, it can be one of the concern contribution to increase students’ English academic achievement through implementation of reading comprehension’s aspects. The teacher needs to implement the aspects of reading comprehension as the focus learning material and synergize it with the other main aspects of English academic achievement.Keywords: Correlation, Reading Comprehension, English Academic Achievement.